Anteseden Kesadaran Konsumen pada Pengguna Transportasi Online - Lina Lina; Fatik Rahayu; Robert Kristaung (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to test and analyze the influence of brand love, brand trust, brand commitment on consumer awareness of online transportation users. The sample used in this research was 250 respondents. The sampling technique used was purposive sampling. Data were analyzed using the Structural Equation Model (SEM) method. The results of this research are (1) Brand Love has a positive effect on Consumer Awareness (2) Brand Trust has a positive effect on Consumer Awareness (3) Brand Commitment has a positive effect on Consumer Awareness. It is hoped that this research can develop insight and knowledge, especially in the field of marketing management, especially regarding brand love, brand commitment, brand trust and consumer awareness and is expected to be used as a means of developing knowledge.